Badania antropometryczne w Instytucie Wzornictwa Przemysłowego - Batogowska, Anna (Polskie Towarzystwo Antropologiczne, 1987)
The article contains a review of the activities carried out by the Institute in the field of measurement methodics and designing of measurement apparatus.
Anthropometric investigations in the Institute of Industrial Design